Influência da salinidade na distribuição e dieta da ictiofauna em um estuário hipersalino - Sales, Natalice dos Santos (2015)
Hypersaline estuarine systems the fish species move between areas of greater supply of resources and according to salinity gradient, because the physiological tolerance is a common adaptation to many species of estuarine fish. Moreover, those species can display other behavioral adaptations, such as food flexibility. Thus, this study analized structure and composition of the ichthyofauna in accordance with the salinity gradients as well as ecology and trophic organization. Samples were collected in rainy and dry season, from January to Decembre 2012, in 12 points distributed into three areas defined according to the salinity gradient (Inferior, Intermediate and Upper). The fishes were captured using a beach seine. The low rainfall, high evaporation rate and the small input of freshwater in Tubarão River estuary favored a salinity between 30 and 45. The structure and composition of ichthyofauna showed spatial and temporal differences between the Tubarão River estuary areas, with salinity and substrate influencing the distribution of species. Atherinella brasiliensis, Lile piquitinga, Eucinostomus argenteus, Ulaema lefroyi, Lutjanus analis and Sphoeroides greeleyi are the most abundant distributed in all the estuarine areas. Among the 104 species caught at the estuary of Tubarão River, 18 were selected according to their abundance, for analysis of trophic ecology. However, only the spacial variation showed significant changes in fish diet. In general, the diet of the species was based mainly on Macroalgae, Polychaeta, Decapoda, Mollusca and Zooplankton. Among these items the representatives of Zooplankton are the main prey in the diet of small juveniles. Because of this preference for certain food items species were grouped into six different trophic guilds: Zooplanktivore, Omnivore, Herbivore-Macroalgae, Zoobenthivore- Hyperbenthos, Zoobenthivore-Epifauna and Zoobenthivore-Infauna. The largest overlap values occured in the Upper zone, due to a higher salinity restricting the establishment of various prey. The results presented in this study showed the direct relationship of the structure and composition of ichthyofauna and the trophic ecology with habitat heterogeneity and the variation in salinity. Thus, the data obtained in the study allows our understanding of the dynamics of community structure that hypersaline system and favors the development of approaches to conservation and sustainable use of biological diversity.